Development of data-processing system for automation of production planning and management process - A. N. Chichko; A. A. Leontjev; V. A. Stasjulevich (Литьë и металлургия)
The work represents the analysis of the data-processing, scheme of the data flow for control over output of OSC Zavod PromBudVod units, shows programme fragments of the developed system and perspectives of its development using Delphi.